(Invited) Group-III Nitrides to the Extreme --- from LEDs and Solar Cells to the Transistor. (13th April 2015) - Bross, Adam; Zhao, Liang; Elsaesser, David; Li, Zhongda; Durniak, Mark; Detchprohm, Theeradetch; Chow, Tat-Sing Paul; Wetzel, Christian
Abstract : Achieving p-type conduction in GaN has poised the material a power semiconductor on all fronts. Record conversion efficiencies and power densities in LEDs render it a platform of GW installation base. After commercial success as a blue light emitter, the emphasis now rests on the expansion of its capacity as a full spectrum direct emitter --- and absorber. Green and amber LEDs will allow full control of lighting quality and specificity in photochemistry. In early results we find evidence of temperature performance crucially superior to those of the incumbent. Next, we explore the same GaInN/GaN quantum wells as a concentration solar cell converter. While definitely limited to the short wavelength range so far, we find respectably high spectral conversion efficiencies and outstanding temperature stability. Such performance, however, is just early indication of what else lies ahead in terms of power electronics in the form of lateral and vertical transistor. In early results we monolithically integrate LED and transistor.